TRADISI SEBARAN APEM KEONG MAS DESA PENGGING KECAMATAN BANYUDONO KABUPATEN BOYOLALI KAJIAN ETNOLINGUISTIK - Gitya Ayuningtyas, Auliana Dwi Rahmah, Imam Baihaqie (JURNAL PENELITIAN PENDIDIKAN SOSIAL HUMANIORA, 2026)
This article examines the Sebaran Apem tradition in Pengging Village, Banyudono subdistrict, Boyolali district from an ethnolinguistic perspective. The tradition, which is routinely held every year in the month of Sapar, is a form of local culture that has been preserved amid the waves of modernization. This study uses a qualitative descriptive approach with in-depth observation and documentation methods. Data analysis uses informal methods with an emphasis on names, meanings, and terms in the tradition. The results show that the Sebaran Apem Keong Mas tradition consists of four main processes: tirakatan, larungan, arak-arakan, and sebaran apem. Each process has a deep cultural meaning related to gratitude, community unity, fertility, and harmony with nature. This study shows that the language structure and naming in the Sebaran Apem Keong Mas tradition reflect how the Pengging community understands and interacts with their world, in accordance with the Sapir-Whorf hypothesis. In conclusion, the Sebaran Apem Keong Mas tradition is not only an annual ritual but also a cultural knowledge system that integrates spiritual, social, and environmental values that remain meaningful as local cultural heritage. Keywords: Ethnolinguistics, Saparan Tradition, Cultural Meaning, Pengging, Local Wisdom